Synergistic Induction of Apoptosis by Quercetin and Curcumin in Chronic Myeloid Leukemia (K562) Cells: II. Signal Transduction Pathways Involved - Altundag, Ergul Mutlu; Yilmaz, Ayse Mine; Serdar, Belgin Sert; Jannuzzi, Ayse Tarbin; Kocturk, Semra; Yalcin, A. Suha (Routledge Journals, Taylor & Francis Ltd, 2021)
Flavonoids are phenolic substances with chemo-preventive and chemotherapeutic properties. They are widely found in fruits and vegetables. The polyphenols quercetin and curcumin have antioxidant, anti-inflammatory, anti-carcinogenic, and pro-apoptotic properties. They were successfully used against different human cancers, especially chronic myeloid leukemia cancer cells. We have previously investigated anti-proliferative and apoptotic effects of quercetin and curcumin combination in K562 cells. Our data showed that they had beneficial synergistic effects. Based on these findings, we aimed to clarify signaling pathways involved in synergistic combination treatment with quercetin and curcumin in these cells. Proteins were investigated by Western blotting and by confocal microscopy. Changes in several genes in 10 different pathways related to cell proliferation, apoptosis, cell cycle, inflammation, hypoxia and oxidative stress were observed. Combination of quercetin and curcumin was effective on genes that were particularly related to p53, NF-kappa B and TGF-alpha pathways. Down-regulatory (CDKN1B, AKT1, IFN-gamma) and up-regulatory (BTG2, CDKN1A, FAS) effects on genes and related protein expressions may provide a multi-targeted therapy potential for chronic myeloid leukemia cancer cells without affecting healthy cells.
Keywords: Kappa-B; Cycle; Death; Bioavailability; Products; Targets; Btg2